Physicochemical and morphological characterization of potato starch (Solanum tuberosum L.) as raw material for the purpose of obtaining bioethanol (2015)
In Colombia, there are geographic areas where the potato crop is the principal economic product. The diversity of potato varieties, has resulted in differences in sizes and in chemical and physical compositions. These variables are defined by genetic factors, agricultural practices, and climatic and soil conditions. The physical characteristics of the different potato varieties are directly related to aspects of production and performance, unlike the chemical composition and morphology of starch granules, which define the nutritional quality and industrial use. In this research, an analysis of the physicochemical and morphological properties of native starches from six potato varieties was carried out, forming a pilot study for the selection of promising varieties for ethanol production. For this purpose, the samples were dried to constant weight. The ash, amylose and amylopectin contents showed significant differences between the varieties. Similarly, differences were observed in the shape and size of the granules, variables that influenced the gelatinization temperature and viscosity of the final products. These variations in the physicochemical properties and morphology of the starches may affect the use of starch and in the production of ethanol.